PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI KONSEP 3B (BRAIN, BEHAVIOR, BEAUTY ) PADA DOSEN DAN KARYAWAN AKS-AKK YOGYAKARTA - Prihatin Saraswati (Jurnal Socia Akademika, 2021)
Research on student perception of the implementation of concept 3 B (Brain, Behavior and Beauty) in employees and Lecturers AKS AKK Yogyakarta is intended to explore the perception of students to the services of lecturers in academic and non-academic fields with the intention of whether students are satisfied with the services provided during lectures at AKS AKK in the Culinary Arts, Fashion Design and Makeup Program so that data can be used as feedback to improve servants at AKS AKK Yogyakarta. This study uses a descriptive interpretive approach. Random sampling pad of the students of the three study programs. The results obtained from this study on the application of the concept of brain, behaviour, beauty students perceive it is good only on the element of adversity quotient and work behaviour on the application of behaviour. The innovative elements are further enhanced